Challenges in mastering academic writing: A case study of English language learners at the University for Business and Technology - Lama, Alma; Suhodolli, Mirsad (Edelweiss Applied Science and Technology, 2024)
This research investigates the problems students of the English Language Faculty at the University for Business and Technology face and proposes certain remedies for academic writing. The paper will try to identify the areas in academic writing that are problematic and detect whether the current strategies of instruction are workable or not and, thus, whether specific improvements are needed. It tries to analyze, namely, the issues EFL students encounter with the writing process, language proficiency, and integration of critical thinking and research during three academic years. In this light, a combination of two methods has been applied for a comprehensive assessment. Data collection is done through the administration of questionnaires to 60 students in their first, second, and third-year levels in the English Language Program. The questionnaire probes into information on the experiences and perceptions of the students concerning their difficulties in academic writing. It also consists of the collection of qualitative data by interviewing six professors of the English Language at UBT about their perceptions of teaching difficulties and the efficiency of currently applied pedagogical approaches. Geographically, the scope of the study is UBT; it will exclusively consider the English Language Program and its related teaching methodologies. Preliminary findings reveal that academic writing does pose numerous problems: in language proficiency, integration of critical thinking, and efficiency through current teaching methodology. The students point to their difficulty in the development of academic writing competencies, while professors emphasize weaknesses in instructional strategies that impede the student's progress. This study, therefore, recommends corrective development in teaching methods and support structures to impact the academic writing competence of EFL students at UBT. Areas have been identified in which current practice is failing, together with recommendations of ways in which instructional methods might be refined. These findings from the research provide the necessary insight for educators here at UBT in terms of teaching methodology and support mechanisms. Addressing identified issues and incorporating proposed improvements will go a long way toward enhancing EFL students' overall academic writing skills for improving their academic standing and enhancing their learning experiences.